PRINSIP DASAR DAN ETIKA DALAM PENELITIAN ILMIAH - Lusi Ayu Gustari; Riswanto, Nur Kholis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the era of digitalization and modernization, the development of knowledge through scientific research is crucial, yet ethical aspects governing its implementation are often overlooked. Research ethics serve as a moral guide that ensures honesty, transparency, and the protection of research subjects' rights. This study employs a literature review method to collect and analyze various sources related to ethics and research principles. The findings indicate that research ethics encompass the moral obligations of researchers to respect subjects, maintain confidentiality, and minimize risks. Additionally, regulations and writing codes of conduct must be implemented to prevent academic misconduct and plagiarism, which can have serious consequences. In conclusion, the proper application of ethics is vital for producing quality research that benefits society.